Differential Change in Hippocampal Radial Astrocytes and Neurogenesis in Shorebirds With Contrasting Migratory Routes - Mendes de Lima, Camila; Douglas Corrêa Pereira, Patrick; Pereira Henrique, Ediely; Augusto de Oliveira, Marcus; Carvalho Paulo, Dario; Silva de Siqueira, Lucas; Guerreiro Diniz, Daniel; Almeida Miranda, Diego; André Damasceno de Melo, Mauro; Gyzely de Morais Magalhães, Nara; Francis Sherry, David; Wanderley Picanço Diniz, Cristovam; et al. (Frontiers in Neuroanatomy, 2019)
Little is known about environmental influences on radial glia-like α cells (radial astrocytes) and their relation to neurogenesis. Because radial glia participates in adult neurogenesis and astrogenesis, we investigated this question in two migratory shorebirds which complete their autumnal migration using contrasting migratory routes. Before their flights to South America, birds make a stopover at the Bay of Fundy in Canada, and from there the semipalmated sandpiper (Calidris pusilla) crosses the Atlantic Ocean in a non-stop 5-day flight, whereas the semipalmated plover (Charadrius semipalmatus) mostly flies overland with stopovers for rest and feeding. We previously demonstrated in these species differential effects of their contrasting flights on the number and morphology of hippocampal stellate astrocytes following migration to South America and reduced hippocampal neurogenesis in C. pusilla during its stopover in the Bay of Fundy before its transatlantic flight. Here we compared the number of young DCX-immunolabeled neurons, the number of stellate astrocytes, and three-dimensional reconstructions of radial glial-like α cells in the hipocampal V region between C. pusilla and C. semipalmatus before and after autumn migration. We found that compared with migrating birds, the morphological complexity of radial glial-like α cells of wintering birds significantly increased in C. semipalmatus and decreased in C. pusilla and this was associated with the total number of DCX young neurons. Compared with migrating birds in the Bay of Fundy, wintering C. pusilla showed significant reduction in the number of hippocampal Type I and Type II astrocytes, whereas C. semipalmatus did not change its total numbers. Although C. pusilla and C. semipalmatus differ phylogenetically and in other ways, it may be significant that morphological complexity of radial astrocytes and neurogenesis of wintering birds was greater in the semipalmated plover which probably relies more on visuospatial information for navigation. We suggest that the continuous non-stop flight of the semipalmated sandpiper and the migratory flight with stopovers for feeding and rest of the semipalmated plover differentially affected radial astrocyte morphology and neurogenesis.